Personalised vs. Non-Personalised Peer Review Requests: Preliminary Data for Calculating Effects on Response Rate, Quality and Completion - Tóth, János József (KOME, 2025)
Peer review is and will remain the cornerstone of research publishing, but finding the right candidate to write an evaluation report for submitted manuscripts can be a challenge for academic publishers. Reaching out to peer reviewers always leaves a written trail (both for reasons of editorial accountability and quality control) and generally starts with an email inquiry from the editors. The content and style of these emails can influence how the recipient responds to the request, and analysing them could offer publishers valuable insights on how to design such initial contacts for optimal efficacy. This article is aimed at presenting a database and preliminary results for such analysis, consisting of 854 anonymised peer review requests sent out through traditional email, academia.edu and researchgate.net private messages between 2018 and 2022. It was found that personalised peer review requests had a higher response rate and higher ratio of submitted reports than non-personalised ones, and personalisation has the best results with peers of low academic seniority. Requests sent through academic social media had a response rate comparable to personalised email messages but received significantly fewer refusals and resulted in more completed evaluation reports, especially when female academics were targeted.